Screw withdrawal of oil palm lumber with different moisture extraction method / Aminuddin Yusof - Yusof, Aminuddin (Faculty of Applied Sciences, 2016)
This report looks at the effect of screw withdrawal of oil palm lumber treated with different moisture extraction method. The oil palm lumber samples were collected from different portions (bottom and middle) and different layers (outer and inner). One type of screw was used. The specimens were prepared and the screw were installed according to ASTM D1761-06 (2012) standards. The dimensions of the specimens were 51 X 51 X 152 mm. the screw withdrawal values showly high significant difference for treatment, portion and layer. Bottom portion give higher maximum load value (565.003N) than middle portion (375.309N). And outer layer value (541.665N) gives higher maximum load value than the inner layer (398.481 N). It also shows the maximum load value for untreated sample (525.684N) higher than ethanol (476.625N) and acetone (407.901 N) treatment.